Delivery of RANKL-Binding Peptide OP3-4 Promotes BMP-2–Induced Maxillary Bone Regeneration. (June 2016) - Uehara, T.; Mise-Omata, S.; Matsui, M.; Tabata, Y.; Murali, R.; Miyashin, M.; Aoki, K.
Although bone morphogenetic protein 2 (BMP-2) is known to stimulate osteogenesis, there is evidence that high doses of BMP-2 can lead to side effects, including inflammation and carcinogenesis. The supplementation of other bone-augmenting agents is considered helpful in preventing such side effects by reducing the amount of BMP-2 required to obtain a sufficient amount of bone. We recently showed that a receptor activator of nuclear factor κB ligand (RANKL)–binding peptide promotes osteoblast differentiation. In the present study, we aimed to investigate whether OP3-4, a RANKL-binding peptide, promotes BMP-2–induced bone formation in the murine maxilla using an injectable gelatin hydrogel (GH) carrier. A GH carrier containing OP3-4 with BMP-2 was subperiosteally injected into the murine maxillary right diastema between the incisor and the first molar. The mice were sacrificed 28 d after the injections. The local bone formation in the OP3-4-BMP-2–injected group was analyzed in comparison to the carrier-injected, BMP-2–injected, and control-peptide-BMP-2–injected groups. The GH carrier containing OP3-4 with BMP-2 enlarged the radio-opaque area and increased the bone mineral content and density in the radiological analyses in comparison to the other experimental groups. Interestingly, fluorescence-based histological analyses revealed that the mineralization had started from the outside, then proceeded inward, suggesting that the size of the newly formed bone had already been set before calcification started and that the effects of OP3-4 might be involved in accelerating the early steps of osteogenesis. Actually, OP3-4 enhanced the BMP-2–induced 5-bromo-2′-deoxyuridine (BrdU)–positive cell numbers at the injected site on day 7 and the expression of Runx2 and Col1a1, which are early osteogenic cell markers, on day 10 after the subperiosteal injections. In summary, we demonstrated, for the first time, that the application of OP3-4 by subperiosteal injection promoted BMP-2–induced bone formation, which could lead to the development of an easy and noninvasive means of promoting alveolar ridge formation.